The concept of settlement sustainability in Kota Baru Parahyangan during the Covid-19 era (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Kota Baru Parahyangan (KBP) is one of the luxury residential areas in West Bandung Regency, developed under the garden city concept. The area is designed to provide a comfortable, green, and integrated living environment. It consists of various residential clusters, educational facilities, commercial centers, and green open spaces. The Covid-19 pandemic triggered changes in residents’ behavior, such as the rise in home-based activities (work from home) and an increased demand for open spaces. In this context, a study of the settlement sustainability concept in KBP becomes crucial, particularly to assess how adaptive and resilient the area has been in facing multidimensional crises. This research aims to examine how KBP endured the pandemic by evaluating aspects of environmental sustainability, architectural design, and economic strategies that support the resilience of the area. The research employs a qualitative-descriptive approach, using literature review, field observation, and interviews with KBP stakeholders. The absence of studies addressing the link between KBP’s residential environment and its sustainability during the Covid-19 pandemic represents a research gap that this study seeks to address. Therefore, between 2021 and 2022, KBP can be regarded as having successfully navigated the challenges of the pandemic through its natural environmental concept, context-appropriate spatial and architectural planning, and effective marketing strategies.
Keywords: Covid-19; Design concept; Kota Baru Parahyangan; Settlement sustainability